Ultra-thin, zoom capable, flexible metalenses with high focusing efficiency and large numerical aperture - Shi Yilin; Dai Hao; Tang Renjie; Chen Zequn; Si Yalan; Ma Hui; Wei Maoliang; Luo Ye; Li Xingyi; Zhao Qing; Ye Yuting; Jian Jialing; et al. (Nanophotonics, 2023)
The ever-growing demand for miniaturized optical systems presents a significant challenge in revolutionizing their core element – the varifocal lens. Recent advancements in ultra-thin, tunable metasurface optics have introduced new approaches to achieving zoom imaging. However, current varifocal metalens have faced challenges such as low focusing efficiency, limited tunability, and complicated designs. Here, we employ the high-contrast transmit arrays (HCTA) structures to design and fabricate a polarization-independent, single-layer flexible metalens that operates at a wavelength of 940 nm. Using a uniform stretching system, we characterized its optical performance to achieve over 60 % focusing efficiency within a 0 %–25 % stretch range, while the focal length changes align with theoretical predictions. Furthermore, our research also successfully demonstrated the capacity of a metalens with a numerical aperture (NA) of 0.5 to efficiently adjust imaging magnification within a 2× range, achieving imaging results that approach the diffraction limit. This research offers promising prospects for the practical use of compact and miniaturized optoelectronic devices in fields like photography, mixed reality, microscopy, and biomedical imaging.